PENGARUH PEMBERIAN EKSTRAK DAN INFUSA DAUN KELOR (Moringa oleifera) TERHADAP KADAR GSH HEPAR MENCIT (Mus musculus) OBESITAS JANTAN YANG DIINDUKSI 2-Nitropropane - Muhammad Nafi (2019)
Obesity can cause low grade chronic inflammation which results in increased ROS, which can lead to hepatocellular cancer. In several studies, it was proven that in the mice liver DNA induced with 2-Nitropropane, showed an increase in reactive oxygen in the liver and was able to cause DNA damage. Oxidative stress damage can be prevented by endogenous antioxidant compounds, one of them is GSH. Antioxidants can also be obtained exogenously from Moringa leaves contain quercetin flavonoids can act as hepatoprotective agents. This research method uses obesity mice which has been given Moringa leaf extract 4mg/kg and 40 mg/kg, respectively.extract (4 mg / kg) and leaf infusion (40 mg / kg). Moringa leaves has been give for 20 days priorly, followed by 2-Nitropropane (0.02 ml/ kg) for 20 days, then induced 2-Nitropropane (0.02 mL / kg). The results showed a decrease GSH in liver, after 2-Nitropropane induction. The levels of GSH in the mice liver which given extracts and Moringa leaf infusion had differences with the control group. We concluded that Moringa leaf extract administration has an effect on GSH level in liver of obese mice which induced by 2-Nitropropane